Kybernetismus: Politische Anthropologie in der Krise. - Riedenauer, Markus (Münchener theologische Zeitschrift, 2024)
Transformations in healthcare policy and in the global economy in connection with digitalization can be interpreted as realizations of a cybernetic paradigm, for which this article proposes the term 'cybernetism'. This implies a political anthropology that is incompatible with the image of man developed by Aristotle through to Habermas and which forms the basis of the liberal, democratic constitutional state. The medical-technocratic image of man reveals the deformative potential of applied sociocybernetics, which contradicts the foundations of democracy.